The Acoustical Design of the Christchurch Town Hall. Issue 1 (March 2014) - Marshall, Harold
The Christchurch Town Hall (New Zealand) was opened on September 30 1972. Disastrous earthquakes hit Christchurch in September 2010 and February 2011. Most of the CBD and the historic buildings were destroyed or damaged by the February event, including much of the Town Hall complex. The City Council in November 2012, resolved to restore the entire building but at the time of writing there remains uncertainty. The intention of this paper is to put on record the history of the Christchurch Town Hall design in case it does not survive the political after-shocks of the earthquakes. With the building's future now in jeopardy it seems appropriate to set out the process that led to this unique design, acknowledge the many contributors, outline its research base, the innovations in predictive technology employed, the evaluation of its acoustical properties and the learning that flowed from it.